Packaging Aesthetics and Brand Personality as Factors Shaping Consumer Preferences for Modern Snack Products in Indonesia - Andiani, Paramita; Nailul, Muhammad (West Science Interdisciplinary Studies, 2025)
This study investigates the influence of packaging aesthetics and brand personality on consumer preferences for modern snack products in Indonesia. As the snack industry becomes increasingly competitive, visual appeal and emotional branding have become key differentiators. Using a quantitative approach, data were collected from 160 respondents through an online questionnaire based on a 5-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3.0). Results show that both packaging aesthetics and brand personality have significant and positive effects on consumer preferences. Brand personality demonstrated a slightly stronger influence, indicating that emotional connection plays a crucial role in shaping consumer choices. The study highlights the importance of integrating visually compelling packaging with a relatable brand personality to enhance consumer appeal and build loyalty in Indonesia’s fast-growing snack market.